2021
DOI: 10.31219/osf.io/mw8y4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The incremental net benefit of lipid-lowering therapy with PCSK9 inhibitors: A Systematic Review and Meta-analysis of cost-utility studies

Abstract: Introduction: Proprotein convertase subtilisin/kexin 9 inhibitors (PCSK9i) are monoclonal antibodies that lower lipid levels by inhibiting PCSK9. Although several cardiovascular outcome trials reported beneficial clinical effectiveness of PCSK9i, the evidence on cost-effectiveness is mixed. We systematically reviewed the evidence on cost-effectiveness and synthesized incremental net benefit (INB) to quantify the pooled cost-effectiveness of PCSK9i lipid-lowering therapy. Methods: We systematically searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We followed the data preparation method and analysis described and used elsewhere 23, 33, 36, 37 . To calculate the INB and its variance, mean values along with dispersions (SD, SE, and 95% CI) of ΔC and ΔE are required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the data preparation method and analysis described and used elsewhere 23, 33, 36, 37 . To calculate the INB and its variance, mean values along with dispersions (SD, SE, and 95% CI) of ΔC and ΔE are required.…”
Section: Methodsmentioning
confidence: 99%
“…A favourable tolerability profile, ease of use, and affordability make Ezetimibe a better option than PCSK9i 22 . Furthermore, a recent meta-analysis of cost-utility studies (CUA) showed PCSK9i to be not cost-effective compared to other lipid-lowering therapeutic agents in high-income countries (HICs) 23, 24 . As a result, Ezetimibe can be used as a next-cholesterol medication.…”
Section: Introductionmentioning
confidence: 99%
“…68 Health economic analyses are essential for evaluating the value of PCSK9 inhibitors to their clinical benefits. 69 The mechanism of action of PCSK9 inhibitors is shown in Figure 5.…”
Section: Pcsk9 Inhibitorsmentioning
confidence: 99%